2000
DOI: 10.1074/jbc.275.15.10851
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Hypochlorous Acid with Tyrosine and Peptidyl-tyrosyl Residues Give Dichlorinated and Aldehydic Products in Addition to 3-Chlorotyrosine

Abstract: The toxicity of hypochlorous acid (HOCl) generated from activated neutrophils has been associated with several pathological processes such as atherosclerosis. Formation of 3-chlorotyrosine (Cl-Tyr) has been used as a marker for assessing the involvement of HOCl in such processes. In this study, we aimed to investigate the formation of Cl-Tyr from reaction of HOCl with tyrosine (both free and peptide-bound) and the fate of Cl-Tyr under such conditions. Tyrosine, N-acetyltyrosine, bovine serum albumin, and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 63 publications
3
65
0
Order By: Relevance
“…50 Interestingly, the diClTyr to ClTyr ratio in lesion lipoproteins was high ( Table 4) compared to that found for reactions of HOCl with free and peptide-bound Tyr. 24 In contrast, analysis of SN-2 after removal of all lipoproteins showed comparatively fewer products and lower ratios of diClTyr to ClTyr (data not shown). A high ratio may be obtained under conditions of high local oxidant production (AJ Kettle, unpublished results), and our data supports the previous suggestion by Heinecke 52 that Tyr chlorination via myeloperoxidase activity is relatively specific for lesion lipoproteins.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…50 Interestingly, the diClTyr to ClTyr ratio in lesion lipoproteins was high ( Table 4) compared to that found for reactions of HOCl with free and peptide-bound Tyr. 24 In contrast, analysis of SN-2 after removal of all lipoproteins showed comparatively fewer products and lower ratios of diClTyr to ClTyr (data not shown). A high ratio may be obtained under conditions of high local oxidant production (AJ Kettle, unpublished results), and our data supports the previous suggestion by Heinecke 52 that Tyr chlorination via myeloperoxidase activity is relatively specific for lesion lipoproteins.…”
Section: Discussionmentioning
confidence: 83%
“…21,22 Artifactual formation of m-Tyr, o-Tyr, DOPA, and diTyr during protein hydrolysis of atherosclerotic tissue using the methodology described herein has been investigated in detail. 21,23,24 The maximum artifactual formation of the analytes determined by this method consistently ranges from 20 mol/mol of m-Tyr, o-Tyr, and diTyr to 200 mol/mol of DOPA per parent amino acid.…”
Section: Hplc Analysesmentioning
confidence: 99%
“…In addition to these kinetic arguments, other processes such as hyperoxidation (19,20) and de-chlorination or metabolism (21,55) could have conceivably contributed to our inability to detect 3-Cl-Tyr in inflamed arteries. Examination of inflamed arterial tissue for dichlorinated species and 4-hydroxyphenylacetaldehydes (19,20) may be useful to assess a potential contribution of tyrosine hyperoxidation.…”
Section: Discussionmentioning
confidence: 91%
“…These include the low rate of reaction of tyrosine and peptidyl-tyrosyl residues with HOCl, with an estimated rate constant of ϳ40 M Ϫ1 s Ϫ1 (18). Also, 3-Cl-Tyr can be oxidized further to 3,5-dichlorotyrosine and mono-and dichlorinated 4-hydroxyphenylacetaldehydes (19,20). Furthermore, in biological systems, 3-Cl-Tyr is subject to metabolism and dechlorination (21).…”
mentioning
confidence: 99%
“…This may be due to either the absence of free Tyr that might cross-link to proteinbound Tyr residues, or the steric constraints that may be imposed on the dimerization of Tyr-derived phenoxyl radicals formed on matrix proteins by the three-dimensional structure of the matrix. A previous study from this laboratory has revealed that di-Tyr can be generated on treatment of the globular protein BSA with HOCl [54], suggesting that that steric factors play an important role in determining the relative yield of di-Tyr in different situations.…”
Section: Discussionmentioning
confidence: 99%